Utilization of red and yellow Coffea arabica var. Caturra pulp: macronutrient analysis, carotenoid extraction, and encapsulation for dairy product enrichment - Rojas-Orduña, Elkin; Hernández-Carrión, María; Gómez-Franco, Juan David; Narváez-Cuenca, Carlos-Eduardo; Sánchez-Camargo, Andrea del Pilar (Frontiers in Nutrition, 2023)
This study aimed to investigate the macronutrient and carotenoid content of red and yellow Coffea arabica var. Caturra pulp, a by-product of coffee processing in Colombia. The study employed ultra-sound-assisted extraction (UAE) to extract carotenoids, and a 23 factorial design was used to evaluate the effects of pulp color, biomass-solvent ratio, and solvent mixture composition on carotenoid content and extraction yield. The condition that provided the highest carotenoid extraction was further encapsulated by spray drying and added to a dairy product. The results showed that coffee pulp has significant dietary fiber content and high levels of carotenoids, with yellow pulp having a higher content than red pulp. Lutein isomers and lutein esters were the most abundant carotenoids found in both red and yellow coffee pulp. The highest carotenoid extraction was achieved using a 1:40 (g/mL) biomass:solvent ratio and a 20:80% v/v Ethanol:Ethyl Acetate solvent mixture for the yellow pulp. The carotenoid extract also demonstrated high encapsulation efficiency (46.57 ± 4.03%) and was found to be stable when added to a fermented milk product. This study presents an alternative solution for utilizing coffee by-products in Colombia, which could positively impact the families of over half a million Colombian coffee producers.